Marketing and Service Promotion Strategy for Customer Satisfaction at Mie Gacoan Restaurant Cirebon - Tessa Aisyatul Hasanah; Afiqoh Agustin (Cirebon International Journal of Economics and Business, 2023)
Indonesian people who really like food that tastes spicy make this gacoan noodle restaurant always crowded with customers. Not only the taste of the food is very popular, this restaurant also sets very affordable prices. This study aims to determine the effect of marketing promotion strategies and to determine the effect of service on customer satisfaction. to determine the extent to which promotion and service to customer satisfaction. This research method is qualitative research, namely research that aims to understand the phenomenon of what is experienced by the research subject. For example, behavior, perception, motivation, action, and others. The results of this study indicate that the popularity of spicy gacoan noodles has attracted many people to this business plan, which can generate up to 50% profit. Many factors make Mie Gacoan. marketing strategies and service menus that suit the tongue of Indonesians who like spicy food but at a price of Rp. 10.000, - you can enjoy your meal at this restaurant.